(untitled) (Communications in Mathematical Research, 2025)
In this note we describe a logarithmic version of mirror LandauGinzburg model for semi-projective toric manifolds and show in an elementary and explicit way that the state space ring of the Landau-Ginzburg mirror is isomorphic to the C-valued cohomology of the toric manifold.